‘You can turn off the light if you’d like’: Pediatric healthcare visits for children with Autism Spectrum Disorder as an interactional achievement - Solomon, Olga (Med Anthropol Q, 2015)
Substantial scholarship has been generated in medical anthropology and other social science fields on typically developing child–parent–doctor interactions during health care visits. This article contributes an ethnographic, longitudinal, discourse analytic account of a child with autism spectrum disorder (ASD)–parent–doctor interactions that occur during pediatric and neurology visits. The analysis shows that when a child with ASD walks into the doctor’s office, the tacit expectations about the visit may have to be renegotiated to facilitate the child’s, the parent’s and the doctor’s participation in the interaction. A successful visit then becomes a hard-won achievement that requires the interactional and relational work of all three participants. We demonstrate that communicative and sensory limitations imposed by ASD present unique challenges to all the participants and consider how health care disparities may invade the pediatric encounter, making visible the structural and interactional processes that engender them.